A Large Chorioangioma can Result in Adverse Perinatal Outcome - Shama Chaudhry; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Chorangioma of the placenta is a common benign vascular tumor of the placenta with a frequency of about 1%. It is threatening as it often goes unnoticed and presents potentially serious fetal risks and making it necessary to keep the pregnancy under surveillance. It usually presents as a solitary nodule or, less frequently, as multiple nodules, consisting of blood vessels and stroma. Most of these tumors are small and have no adverse effects on the fetus. Large tumors are associated with complications affecting mother and the fetus which may cause sudden intrauterine fetal death. Chorangiomas act as peripheral shunts between arteries and veins, leading to progressive heart failure of the fetus. In the case prenatal diagnosis is achieved by ultrasonography and Doppler studies are used confirm the highly vascular nature of the mass. As the tumor is associated with unfavorable side-effects on the mother and fetus like polyhydroamnios, prematurity, toxemia, hydrops, fetal heart failure and, intra uterine death, regular monitoring is required to detect and manage complications early on in the pregnancy. A large size of the tumor is indicative of a higher probability of complications. The case presented is that of a large chorioangioma in a primigravida without any serious complications and a successful outcome. KEY WORDS: Chorangioma, Placental Tumor, Toxemia, Hydrops Fetalis, Intrauterine Fetal Death